2022
DOI: 10.3390/diagnostics13010030
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of the Effects of SMILE with Different Amounts of Stromal Ablation on Corneal Biomechanics by Optical Coherence Elastography

Abstract: This work aims to depth-resolved quantitatively analyze the effect of different stromal ablation amounts on the corneal biomechanical properties during small incision lenticule extraction (SMILE) using optical coherence elastography (OCE). A 4.5-MHz ultrasonic transducer was used to excite elastic waves in the corneal tissue. The OCE system combined with the antisymmetric Lamb wave model was employed to achieve a high-resolution, high-sensitivity, and depth-resolved quantitative detection of the corneal Young’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…The phase velocity in healthy corneal tissue gradually decreases from the anterior surface to the endothelium, with an average value of 3.96 ± 0.27 m/s, which is consistent with the results reported in the previous literature. 25 , 38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase velocity in healthy corneal tissue gradually decreases from the anterior surface to the endothelium, with an average value of 3.96 ± 0.27 m/s, which is consistent with the results reported in the previous literature. 25 , 38 …”
Section: Resultsmentioning
confidence: 99%
“…Elastography is another emerging technique for evaluating the corneal biomechanics, including ultrasonic elastography, Brillouin microscopy, and optical coherence elastography (OCE). 24 , 25 Qian et al 26 used a confocal 40-MH needle ultrasound transducer to assess the corneal Young's modulus after formalin treatment at different IOPs. Weng et al 27 used a high-frequency ultrasound array method for ultrafast ultrasound imaging and a Lamb wave model to assess the porcine cornea viscoelasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the development of advanced ultrasound transducer technology [23,24], there are some papers have reported that different parameters of acoustic radiation force excitation have been widely used for dynamic elastography of ocular tissue [12,14,15]. However, the large size of the centimeter-scale ultrasound transducer requires the eye and the ultrasound transducer to be immersed in a coupling agent (saline or ultrasound gel) during the experiment, which not only changes the IOP but also changes the boundary conditions of the eye tissue, introducing errors in the assessment of the elastic modulus [25]. In addition, conventional ring array focused ultrasound transducers generally have multiple elements to achieve focused excitation at different working distances, and the more transmitting facet elements produce higher acoustic power, so the power at the focal point of these focused ultrasonic transducers is relatively high [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…A home-build phase-sensitive OCT system combined with an M-B scan model is used to detect the SRW propagation process, as previously described. 57,58 The OCT system had an A-line rate of 50 kHz, a center wavelength of 1310 nm, a scan range of 100 nm, an spatial resolution of 5.7 μ m (axial) × 15 μ m (lateral), an image depth of 5 mm (in air), a signal-to-noise ratio (SNR) of 105 dB, and a displacement sensitivity of 13 nm. In the M-B scan model, each M-scan consisted of 500 A-scans (a total of 10 ms), the B-scan consisted of 1000 M-scans along the lateral axis (a total of 10 s), and 512 sample points in depth will be completed.…”
Section: Methodsmentioning
confidence: 99%